THE ANALYSIS OF THE CITY-COUNTRY RELATIONSHIP AND THE URBAN-RURAL DYNAMICS IN THE MUNICIPALITY OF ILHA SOLTEIRA (SP) - Rosa, Audrey Ferreira [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2018)
The discussion about urban-rural relationship and its dialectical pair is not recent. Many studies have tried to define both, country and city and the relationships among them, using different conceptions and theories. In this regard, a bibliographic review was carried out along this article, in which a host of ways of understanding the urban and rural areas are identified, given the complexity of this issue from the point of view of the diversity of existing relations. Adding to this analysis, we have studied the municipality of Ilha Solteira (SP), which has allowed us to understand the relationship among the city and the countryside, contributing to its formation, designed as a residence for employees from Companhia Energetica do Estado de Sao Paulo (CESP), following a distribution pattern of the residences, according to the professional levels of these workers, and the installation of the Green Belt that would allow its self-sufficiency, and the settlement on Ilha da Estrela in 2005. Thus, based on the theoretical and empirical analysis of the municipality, we have sought to understand the city and the field relationship in the municipality of Ilha Solteira (SP), pointing out the changes which have taken place as well as how these changes have also contributed to the need of conceptual changes to explain the recent phenomena.
Keywords: City-field; Urban-rural; Peri-urban space; Ilha Solteira (Sao Paulo)